Effects of Interfaces of Goethite and Humic Acid-Goethite Complex on Microbial Degradation of Methyl Parathion - Zhao, Gang; Li, Enze; Li, Jianjun; Xu, Meiying; Huang, Qiaoyun; Rong, Xingmin (Frontiers in Microbiology, 2018)
Microbial degradation plays an essential role in the removal of hydrophobic organic compounds (HOCs) dispersed in soil and sediment, and its performance is greatly affected by mineral particles which regulate HOCs bioavailability by interfacial adsorption. Likewise, bacteria cells attach to the surfaces of mineral particles as well but how bacterial attachment affects biodegradation is largely unknown. Here we report inhibitory effects of goethite and humic acid (HA)-goethite complex addition on microbial degradation of methyl parathion (MP). Using attenuated total reflectance-Fourier transform infrared spectroscopy, we observed that the adhesion of bacterial cells responsible for MP degradation on goethite occurred and the adhesive strength increased over time. We then replaced goethite with phosphate-adsorbed goethite to weaken the goethite-bacteria association and the inhibition of MP biodegradation was alleviated. These results suggested the formation of goethite-bacteria association hinder MP biodegradation. Meanwhile, our results showed that HA coating prevented bacterial attachment on goethite particles along with a drastically increased MP adsorption by goethite. The combined effect would lead to decreased mass fluxes of MP to bacterial cells and could represent another mechanism responsible for the decreased degradation rate observed in the current study.